Milagre que se fez...: um estudo dos 36 ex-votos ofertados ao Senhor Bom Jesus de Matosinhos em Congonhas | MG - Thiago de Pinho Botelho (2013)
The present work is concerned about the study of 36 votive (ex-vote) paintings, made of wooden planks, offered to the Lord Bom Jesus de Matosinhos in the Sanctuary of same invocation at Congonhas / MG. Considering the artistic and historical importance of the collection, studies have been conducted on the formal, material and technique composition, going deeply in the Christs iconography (Bom Jesus de Matosinhos) that are shown in these devotional paintings. The collection of 36 votive (ex-votes) belongs to a set of 89 votive paintings that are placed under SPHAN, current IPHAN, trust since 1989 dating from the eighteenth century to the twentieth century and are put up in the Sala dos Milagres.